Perbedaan Rerata Rasio Kadar Natrium Kalium Maternal Antara Preeklamsia Berat Dan Eklamsia - Syaputra, Gunawan Efri; Djanas, Dovy (Andalas Obstetrics And Gynecology Journal, 2020)
Background: Preeclampsia is a pregnancy-specific syndrome in the form of reduced organ perfusion due to vasospasm and endothelial activation that occurs after 20 weeks of gestational age. eclampsia is the occurrence of seizures in a woman with preeclampsia, Sodium (Na +) and Potassium (K +) play an important role in preeclampsia and eclampsia.Objective: To see the difference in mean sodium potassium ratio between pregnancy with severe preeclampsia and eclampsia.Methods: The study was analytic descriptive using a cross sectional study design by looking at the medical records of the subjects according to the time and place of the study. Samples are all medical records of pregnant women who suffer from pre-eclampsia and eclampsia in the obstetric and gynecology section ofÂ  RSUP DR.M.Djamil padang in the period of 15 January 2016 to 31 December 2017, the values of which are sodium, potassium levels and sodium and potassium ratios. Samples were taken from populations that met the inclusion criteria and did not have exclusion criteria. Sampling using a consecuvite sampling technique which was taken from the medical records of RSUP DR. M. Djamil Padang Statistical analysis to assess significance using the T-test.Results: In the Severe preeclampsia and Eclampsia groups it was found that multipara parity had the highest respondents. This is in accordance with the literature where the incidence of preeclampsia is more often found at near term gestational age.Conclusion: There is no significant difference in the average sodium potassium ratio between Severe preeclampsia and EclampsiaKeywords: Severe preeclampsia, eclampsia, sodium and potassium